Artificial leather, its manufacturing method, automobile interior materials, automobile parts, and clothing
Patent Information
- Application Number
- JP2024510727
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-02-07
- Filing Date
- 2024-02-05
- Publication Date
- 2025-03-27
- Estimated Expiration
- 2044-02-05
AI Technical Summary
【0012】 本発明によれば、極細繊維発現型繊維を構成する易溶解性ポリマーに共重合ポリエステルを適用した製造プロセスを用いながらも、緻密で優美な表面品位を有し、良好なタッチ感と耐摩耗性とを両立した人工皮革を得られる。本発明の人工皮革は、自動車内装材や自動車部品、インテリア、コンシューマーエレクトロニクス、衣料などの幅広い用途に用いることができるが、上記のとおり緻密で優美な表面品位を有し、良好なタッチ感と耐摩耗性とを両立することから、特に自動車内装材や自動車部品、インテリア用途に好適に用いることができる。
Smart Images

Figure 0007652336000003 
Figure 0007652336000001 
Figure 0007652336000002
Abstract
Description
[Technical field]
[0001] The present invention relates to artificial leather, a method for producing the same, an automobile interior material, an automobile part, and clothing. [Background technology]
[0002] Artificial leather with a natural leather look, which is mainly composed of a fiber entanglement composed of ultrafine fibers and a polymer elastomer, has superior characteristics compared to natural leather, such as high durability and uniformity of quality. For this reason, it is used in a wide range of applications, such as automotive interior materials and interiors, consumer electronics, and clothing, and its use is expanding year by year. In particular, when artificial leather is used for automotive interior materials and interiors, it is required to have excellent surface quality, as well as a good touch and high abrasion resistance that can withstand practical use.
[0003] Furthermore, due to the recent increase in environmental awareness, environmentally friendly manufacturing processes that reduce the use of organic solvents have been attracting attention in the production of artificial leather. For example, in the case of ultrafine fiber-producing fibers, various studies have been conducted on attempts to use copolymerized polyester-based polymers that are easily dissolved by alkali treatment when producing ultrafine fibers.
[0004] For example, Patent Document 1 proposes a method for producing an artificial leather in which a specific copolyester is used as a sea part polymer to remove the sea part polymer from a fiber-entangled body including islands-in-sea type composite fibers as a constituent component, thereby producing ultrafine fibers having a specific average single fiber diameter, and at least a part of the ultrafine fibers has specific grooves on the surface. It also describes that this method makes it possible to produce an artificial leather having high strength, excellent abrasion resistance, and good texture.
[0005] Patent Document 2 proposes a method for producing ultrafine fiber-generating fibers, in which polyalkylene glycol is added to a sea part polymer and an island part polymer during melt spinning of an islands-in-sea type composite fiber, and the resulting composite fiber is spun. It also describes that the ultrafine fibers obtained by this method can be used to obtain artificial leather having good surface quality and abrasion resistance. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Patent Application Publication No. 2021-155885 [Patent Document 2] Japanese Patent Application Publication No. 2014-231650 Summary of the Invention [Problem to be solved by the invention]
[0007] In the technology disclosed in Patent Document 1, at least a part of the ultrafine fibers constituting the artificial leather has grooves on the fiber surface, which makes it easier for the ultrafine fibers to grip the polymer elastomer, thereby achieving a soft feel and excellent abrasion resistance. However, since the ultrafine fibers have grooves, there is room for improvement in terms of surface quality and touch.
[0008] In the technology disclosed in Patent Document 2, polyalkylene glycol is added to the sea part polymer during melt spinning of islands-in-sea type composite fibers, and then the fibers are spun to form highly rigid ultrafine fibers having a specific range of crystallinity and mobile amorphous content, and the entanglement efficiency is increased, thereby achieving good surface quality and excellent abrasion resistance. However, since polyalkylene glycol with a large number average molecular weight is added during spinning, the dispersibility of polyalkylene glycol in the sea part polymer tends to be insufficient, and it is difficult to obtain a uniform and sufficient sea-removal effect during alkali treatment, leaving room for improvement in surface quality and touch.
[0009] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide an artificial leather and a manufacturing method thereof which have a dense and elegant surface quality and which combine a good touch and abrasion resistance, while being produced through a manufacturing process which applies a copolymer polyester to a readily soluble polymer that constitutes an ultrafine fiber-producing fiber. [Means for solving the problem]
[0010] As a result of the inventors' repeated investigations to achieve the above object, it was found that by stretching ultrafine fiber-producing fibers obtained by copolymerizing a polyalkylene glycol having a specific number average molecular weight with an easily soluble polymer, and then heating the ultrafine fiber-producing fibers at a specific temperature to cause shrinkage, the degree of molecular orientation of the ultrafine fibers constituting the artificial leather obtained through the subsequent steps can be set within a specific range.The inventors also found that within the above range of the degree of molecular orientation, the ultrafine fiber-producing fibers can be made to have good shrinkability, and the obtained ultrafine fibers can have excellent strength, and therefore it is possible to obtain an artificial leather having a dense and elegant surface quality and having both a good touch and abrasion resistance, and thus arrived at the present invention.
[0011] The present invention has been completed based on these findings, and provides the following inventions. [1] An artificial leather comprising, as components, a fiber-entangled body made of ultrafine fibers containing a thermoplastic resin and having an average single fiber diameter of 0.1 μm or more and 10.0 μm or less, and a polymer elastomer, wherein the degree of molecular orientation in the ultrafine fibers is 6.5 or more and 9.0 or less. [2] The artificial leather according to [1], wherein the thermoplastic resin is a polyester resin, and the degree of crystal orientation of the (010) plane and the degree of crystal orientation of the (100) plane in the fiber structure are 0.80 or more and 0.95 or less. [3] The artificial leather according to [1] or [2], wherein the thermoplastic resin is a polyester resin, the crystallite size of the (010) plane in the fiber structure is 2.0 nm or more and 5.0 nm or less, and the crystallite size of the (100) plane is 1.0 nm or more and 4.0 nm or less. [4] The artificial leather according to any one of the above [1] to [3], wherein at least one surface of the artificial leather has nap, and the nap length of the surface is 200 μm or more and 500 μm or less. [5] A method for producing an artificial leather according to any one of [1] to [4] above, comprising the steps of: drawing an ultrafine fiber-producing fiber formed from an easily soluble polymer, which is a copolymer polyester copolymerized with a polyalkylene glycol having a number average molecular weight of 500 to 3,500, and a poorly soluble polymer, to obtain a drawn conjugated fiber; heating the drawn conjugated fiber under conditions such that the surface temperature of the drawn conjugated fiber is 40° C. to 80° C., and then imparting crimping to obtain a crimped conjugated fiber; forming a fiber web from the crimped conjugated fiber and entangling the fiber web to form an entangled conjugated fiber body; expressing ultrafine fibers having an average single fiber diameter of 0.1 μm to 10.0 μm from the entangled conjugated fiber body to form a fiber-entangled body; and imparting a polymer elastomer to the entangled conjugated fiber body or the entangled fiber body. [6] An automobile interior material comprising the artificial leather according to any one of [1] to [4] above. [7] An automobile part comprising the artificial leather according to any one of [1] to [4] above. [8] Clothing comprising the artificial leather described in any one of [1] to [4] above. Effect of the Invention
[0012] According to the present invention, an artificial leather having a dense and elegant surface quality and having both a good touch feeling and abrasion resistance can be obtained, even though a production process is used in which a copolymer polyester is applied to the easily soluble polymer constituting the ultrafine fiber-producing fiber. The artificial leather of the present invention can be used for a wide range of applications, such as automobile interior materials, automobile parts, interiors, consumer electronics, and clothing, but since it has a dense and elegant surface quality and has both a good touch feeling and abrasion resistance as described above, it can be particularly suitably used for automobile interior materials, automobile parts, and interior applications. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a schematic cross-sectional view illustrating a method for measuring the average nap length of the artificial leather of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The artificial leather of the present invention is an artificial leather containing as its components a fiber-entangled body made of ultrafine fibers containing a thermoplastic resin and having an average single fiber diameter of 0.1 μm to 10.0 μm, and a polymer elastomer, and the ultrafine fibers have a degree of molecular orientation of 6.5 to 9.0. These components are described in detail below, but the present invention is not limited to the scope described below as long as it does not deviate from the gist of the invention, and various modifications are possible without departing from the gist of the invention.
[0015] [Fiber entanglement] The artificial leather according to one embodiment of the present invention (hereinafter also referred to as the "present embodiment") includes, as a component, a fiber-entangled body composed of ultrafine fibers containing a thermoplastic resin. Examples of the thermoplastic resin include polyester resin, polyamide resin, polyolefin resin, acrylic resin, polyphenylene sulfide resin, and the like. Examples of the polyester resin include polyethylene terephthalate, polybutylene terephthalate, polytrimethylene terephthalate, polylactic acid, and mixtures and copolymers of these polyester resins. Examples of the polyamide resin include polyamide 6, polyamide 66, polyamide 610, polyamide 12, and mixtures and copolymers of these polyamide resins. Examples of the polyolefin resin include polyethylene and polypropylene, and mixtures and copolymers of these polyolefin resins. Among these, polyester resin is preferably used from the viewpoints of strength, dimensional stability, and heat resistance.
[0016] In this embodiment, examples of the dicarboxylic acid and / or its ester-forming derivative used in the polyester resin include terephthalic acid, isophthalic acid, 2,6-naphthalenedicarboxylic acid, diphenyl-4,4'-dicarboxylic acid and its ester-forming derivative. The ester-forming derivative in this embodiment is a lower alkyl ester, acid anhydride, acyl chloride, etc. of these dicarboxylic acids, and specifically, methyl ester, ethyl ester, hydroxyethyl ester, etc. are preferably used. A more preferred embodiment of the dicarboxylic acid and / or its ester-forming derivative used in this embodiment is terephthalic acid and / or its dimethyl ester. In this embodiment, examples of the diol used in the polyester resin include ethylene glycol, 1,3-propanediol, 1,4-butanediol, and cyclohexanedimethanol, and among these, ethylene glycol is preferably used.
[0017] The thermoplastic resin may contain inorganic particles such as titanium oxide particles, lubricants, pigments, heat stabilizers, ultraviolet absorbers, conductive agents, heat storage agents, antibacterial agents, etc., depending on various purposes, as long as the purpose of the present invention is not impaired.
[0018] The cross-sectional shape of the ultrafine fibers may be either a round cross section or an irregular cross section. Specific examples of irregular cross sections include oval, polygonal such as flat and triangular, sectoral and cross-shaped, hollow, Y-shaped, T-shaped, and U-shaped.
[0019] In this embodiment, the average single fiber diameter of the ultrafine fibers is 0.1 μm or more and 10.0 μm or less. By setting the average single fiber diameter of the ultrafine fibers to 0.1 μm or more, preferably 0.2 μm or more, and more preferably 0.5 μm or more, the artificial leather has excellent color development and light resistance after dyeing. On the other hand, by setting the average single fiber diameter of the ultrafine fibers to 10.0 μm or less, preferably 8.0 μm or less, and more preferably 6.0 μm or less, the artificial leather has a dense surface quality and an excellent touch.
[0020] The average single fiber diameter of the ultrafine fibers is calculated by the following method. (1) A cross section of the artificial leather cut in the thickness direction is observed using a scanning electron microscope (SEM, for example, the "VHX-D500 / D510" model manufactured by Keyence Corporation). (2) Thirty ultrafine fibers are randomly selected from the observation area, and the single fiber diameter is measured from the cross section of each ultrafine fiber. However, when polyester ultrafine fibers with atypical cross sections are used, the cross section of the single fiber is first measured, and the diameter of the cross section is calculated by the following formula when the cross section is considered to be circular to obtain the single fiber diameter. Single fiber diameter (μm) = (4 × (cross-sectional area of single fiber (μm 2 )) / π) 1 / 2 (3) The arithmetic average value (μm) of the 30 obtained fibers is calculated, and the value rounded off to one decimal place is regarded as the average single fiber diameter (μm) of the ultrafine fibers.
[0021] In the artificial leather of this embodiment, the molecular orientation degree of the ultrafine fibers is 6.5 or more and 9.0 or less. When the molecular orientation degree of the ultrafine fibers is 6.5 or more, preferably 6.7 or more, more preferably 7.0 or more, the ultrafine fibers have sufficient strength, resulting in an artificial leather with high strength and excellent wear resistance. On the other hand, when the molecular orientation degree of the ultrafine fibers is 9.0 or less, preferably 8.8 or less, more preferably 8.5 or less, the ultrafine fibers do not become too rigid, resulting in good processability during the production of the artificial leather, and resulting in an artificial leather with excellent moldability and touch.
[0022] In this embodiment, the degree of molecular orientation in the ultrafine fibers is measured by laser Raman spectroscopy and is calculated by the following method. Here, Raman scattering is strong when the vibration direction of the molecular chain and the polarization direction of the incident light are the same, so the scattering intensity of the Raman band belonging to the vibration mode parallel to the molecular chain changes in correlation with the degree of orientation. Therefore, measurements are performed in a polarization direction parallel to the fiber axis and a polarization direction perpendicular to the fiber axis, and the ratio of the intensities is calculated as a parameter (degree of molecular orientation) that correlates with the degree of orientation in the fiber axis direction. The higher the degree of molecular orientation, the larger this parameter becomes, and when there is no orientation, it is 1.
[0023] (1) Ten ultrafine fibers are taken from the artificial leather, and the fiber surfaces of the ultrafine fibers are irradiated with laser light using a laser Raman spectrometer (for example, Jobin Yvon's "Ramanor T64000"). The orientation degree is measured under polarized conditions. (2) When the polarization direction is the same as the fiber axis, it is considered as a parallel condition, and when it is perpendicular, it is considered as a perpendicular condition. From the ratio of the Raman band intensities obtained, calculate the degree of orientation using the following formula, and round the value to one decimal place to obtain the degree of molecular orientation in the ultrafine fibers. Molecular orientation degree=I 平行 / I 垂直 I 平行 : Intensity of the Raman bands attributable to vibration modes parallel to the molecular chain in a deflection arrangement parallel to the fiber axis I 垂直 : Intensity of the Raman bands attributable to vibration modes parallel to the molecular chains in a deflection configuration perpendicular to the fiber axis.
[0024] The degree of molecular orientation in the ultrafine fibers can be adjusted to the above range by adjusting, for example, the spinning speed, draw ratio, draw temperature, heat treatment temperature, and the like.
[0025] In this embodiment, the thermoplastic resin is preferably a polyester resin, and the degree of crystal orientation of the (010) plane and the degree of crystal orientation of the (100) plane in the fiber structure are preferably 0.80 or more and 0.95 or less. When the degree of crystal orientation of the (010) plane and the degree of crystal orientation of the (100) plane in the fiber structure of the ultrafine fibers are preferably 0.80 or more, more preferably 0.82 or more, an artificial leather with high strength and excellent wear resistance is obtained. On the other hand, when the degree of crystal orientation of the (010) plane and the degree of crystal orientation of the (100) plane in the fiber structure of the ultrafine fibers are preferably 0.95 or less, more preferably 0.90 or less, an artificial leather with excellent moldability and touch is obtained.
[0026] In this embodiment, the crystal orientation degrees of the (010) plane and the (100) plane in the fiber structure of the ultrafine fibers refer to values measured and calculated by the following method using a wide-angle X-ray diffraction method. (1) Ultrafine fibers are collected from the artificial leather, and using an X-ray diffractometer (such as the Rigaku Corporation's "SmartLab" X-ray generator), continuous scanning is performed at diffraction angles 2θ from 5° to 60° to draw a diffraction intensity curve. (2) In the above diffraction intensity curve, the crystal diffraction peaks (reflection planes) detected at 2θ = approximately 17° and 2θ = approximately 25° are defined as the (010) plane and the (100) plane, respectively, and the half-width of the diffraction peaks of the diffraction intensity curve obtained by performing continuous scanning from 90° to 270° in the azimuth angle (circumferential) direction for each reflection plane is calculated. (3) From the half-width, the crystal orientation degrees of the (010) and (100) planes are calculated using the following formula, and the value rounded off to one decimal place is regarded as the crystal orientation degrees of the (010) and (100) planes in the fiber structure of the ultrafine fibers. Crystal orientation degree = (180 - half width) / 180.
[0027] The crystal orientation degrees of the (010) and (100) planes in the fiber structure of the ultrafine fibers can be adjusted to be within the above ranges by, for example, adjusting the spinning speed, draw ratio, draw temperature, heat treatment temperature, etc.
[0028] In this embodiment, the thermoplastic resin is a polyester resin, and the crystallite size of the (010) plane in the fiber structure is preferably 2.0 nm or more and 5.0 nm or less, and the crystallite size of the (100) plane is preferably 1.0 nm or more and 4.0 nm or less. The crystallite size of the (010) plane in the fiber structure of the ultrafine fiber is preferably 2.0 nm or more, more preferably 2.5 nm or more, or the crystallite size of the (100) plane is preferably 1.0 nm or more, more preferably 1.5 nm or more, so that the artificial leather has excellent wear resistance. On the other hand, the crystallite size of the (010) plane in the fiber structure of the ultrafine fiber is preferably 5.0 nm or less, more preferably 4.5 nm or less, or the crystallite size of the (100) plane is preferably 4.0 nm or less, more preferably 3.5 nm or less, so that the ultrafine fiber can exhibit good shrinkage, and the artificial leather has a high surface quality.
[0029] In the present invention, the crystallite sizes of the (010) and (100) planes in the fiber structure of the ultrafine fibers refer to values measured and calculated by the following method using a wide-angle X-ray diffraction method. (1) Ultrafine fibers are collected from the artificial leather, and using an X-ray diffractometer (such as the Rigaku Corporation's "SmartLab" X-ray generator), continuous scanning is performed at diffraction angles 2θ from 5° to 60° to draw a diffraction intensity curve. (2) In the above diffraction intensity curve, the crystal diffraction peaks (reflection planes) detected at 2θ = approximately 17° and 2θ = approximately 25° are determined to be the (010) plane and the (100) plane, respectively, and the half-width of the diffraction peak of each reflection plane is calculated. (3) From the half-width, the crystallite sizes of the (010) and (100) planes are calculated using the following formula, and the value rounded off to one decimal place is regarded as the crystallite size (nm) of the (010) and (100) planes in the fiber structure of the ultrafine fibers. Crystallite size (nm) = 0.9 × λ / (β × cosθ) β = (β e 2 -β0 2 ) 1 / 2 Here, λ is the wavelength of the X-ray (nm), θ is the Bragg angle, and β e β0 is the half-width corrected value (0.46° in the present invention).
[0030] The crystallite sizes of the (010) and (100) planes in the fiber structure of the ultrafine fibers can be adjusted to the above ranges by, for example, adjusting the spinning speed, draw ratio, draw temperature, heat treatment temperature, etc.
[0031] The artificial leather of the present embodiment has a fiber entanglement form made of the ultrafine fibers, and when the surface is raised by the method described below, the artificial leather can have a dense and elegant surface quality and a soft texture. As described below, the fiber entanglement is formed from a composite fiber entanglement, which is a precursor of the fiber entanglement. Examples of the composite fiber entanglement include a short fiber entanglement obtained by forming a laminated fiber web from short fibers using a card or cross wrapper and then subjecting the laminated fiber web to needle punching or water jet punching, a long fiber entanglement obtained by a spunbonding method or a melt blowing method, and an entanglement obtained by a papermaking method. The fiber entanglement can be formed by expressing ultrafine fibers from the ultrafine fiber-expressing fibers that constitute the composite fiber entanglement. In particular, when the composite fiber entanglement is a short fiber entanglement, the fibers oriented in the thickness direction of the artificial leather can be increased compared to other entanglements, and the artificial leather has a high density and a good touch on the surface of the artificial leather when raised. Furthermore, the artificial leather has good thickness uniformity and the like.
[0032] When a short fiber entanglement is used, the fiber length of the ultrafine fibers constituting the short fiber entanglement is preferably 25 mm or more and 90 mm or less. When the fiber length of the ultrafine fibers is preferably 25 mm or more, more preferably 35 mm or more, and even more preferably 40 mm or more, the artificial leather has excellent abrasion resistance due to the entanglement. Also, when the fiber length of the ultrafine fibers is preferably 90 mm or less, more preferably 80 mm or less, and even more preferably 70 mm or less, the artificial leather has good surface quality and texture.
[0033] In this embodiment, the ultrafine fibers constituting the short fiber entanglement body may contain various additives depending on the purpose.
[0034] In the artificial leather of this embodiment, for the purpose of improving its strength and shape stability, a woven or knitted fabric may be inserted into, laminated on, or lined with the inside of the entangled composite fiber body.
[0035] [Polymer elastomer] The artificial leather of this embodiment contains a polymeric elastomer as a component. The binder effect of this polymeric elastomer not only prevents the ultrafine fibers from falling out of the artificial leather, but also makes it possible to impart an appropriate sense of resilience.
[0036] Examples of the polymeric elastomer include polyurethane, polyurea, polyacrylic acid, etc., and polyurethane is preferably used from the viewpoints of durability and flexibility. The polymeric elastomer may contain a plurality of polymeric elastomers.
[0037] In the present embodiment, when polyurethane is used as the polymeric elastomer, either an organic solvent-based polyurethane, which is used in a dissolved state in an organic solvent, or a water-dispersed polyurethane, which is used in a dispersed state in water, can be used. From the viewpoint of environmental consideration, however, the use of a water-dispersed polyurethane is preferred.
[0038] When using a water-dispersed polyurethane, it is more preferable to use a water-dispersed polyurethane obtained by reacting a polymer polyol described later, an organic diisocyanate, and an active hydrogen component-containing compound having a hydrophilic group to form a hydrophilic prepolymer, and then adding and reacting a chain extender to obtain a polyurethane precursor, and then reacting the polyurethane precursor with a crosslinking agent. These will be described in detail below.
[0039] (a) Polymer polyol Examples of the polymer polyol preferably used in this embodiment include polyether polyols, polyester polyols, and polycarbonate polyols.
[0040] First, examples of polyether polyols include polyols obtained by addition polymerization of monomers such as ethylene oxide, propylene oxide, butylene oxide, styrene oxide, tetrahydrofuran, epichlorohydrin, and cyclohexylene using polyhydric alcohols or polyamines as initiators, and polyols obtained by ring-opening polymerization of the above-mentioned monomers using protonic acids, Lewis acids, cationic catalysts, etc. as catalysts. Specific examples include polyethylene glycol, polypropylene glycol, polytetramethylene glycol, etc., and copolymer polyols combining these.
[0041] Examples of polyester polyols include polyester polyols obtained by condensing various low molecular weight polyols with polybasic acids, and polyols obtained by depolymerization of lactones.
[0042] Examples of low molecular weight polyols used in polyester polyols include linear alkylene glycols such as ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1.8-octanediol, 1,9-nonanediol, and 1,10-decanediol, branched alkylene glycols such as neopentyl glycol, 3-methyl-1,5-pentanediol, 2,4-diethyl-1,5-pentanediol, and 2-methyl-1,8-octanediol, alicyclic diols such as 1,4-cyclohexanediol, and aromatic dihydric alcohols such as 1,4-bis(β-hydroxyethoxy)benzene. In addition, adducts obtained by adding various alkylene oxides to bisphenol A can also be used as low molecular weight polyols.
[0043] On the other hand, examples of the polybasic acid used in the polyester polyol include one or more selected from the group consisting of succinic acid, maleic acid, adipic acid, glutaric acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, dodecanedicarboxylic acid, phthalic acid, isophthalic acid, terephthalic acid, and hexahydroisophthalic acid.
[0044] Examples of the polycarbonate-based polyol include compounds obtained by reacting a polyol with a carbonate compound, such as a polyol with a dialkyl carbonate or a polyol with a diaryl carbonate.
[0045] The polyol used in the polycarbonate polyol may be a low molecular weight polyol used in the polyester polyol. On the other hand, the dialkyl carbonate may be dimethyl carbonate or diethyl carbonate, and the diaryl carbonate may be diphenyl carbonate.
[0046] The number average molecular weight of the polymer polyol preferably used in this embodiment is preferably 500 or more and 5000 or less. By making the number average molecular weight of the polymer polyol preferably 500 or more, more preferably 1500 or more, it is possible to easily prevent the texture of the artificial leather from becoming hard. On the other hand, by making the number average molecular weight preferably 5000 or less, more preferably 4000 or less, it is possible to easily maintain the strength of the water-dispersed polyurethane as a binder.
[0047] (b) Organic diisocyanate Organic diisocyanates preferably used in the present embodiment include aromatic diisocyanates having a carbon number of 6 to 20 (excluding carbons in isocyanate (NCO) groups, the same applies below), aliphatic diisocyanates having a carbon number of 2 to 18, alicyclic diisocyanates having a carbon number of 4 to 15, araliphatic diisocyanates having a carbon number of 8 to 15, modified products of these diisocyanates (carbodiimide modified products, urethane modified products, urethodione modified products, etc.), and mixtures of two or more of these.
[0048] Specific examples of the aromatic diisocyanate having 6 or more and 20 or less carbon atoms include 1,3- and / or 1,4-phenylene diisocyanate, 2,4- and / or 2,6-tolylene diisocyanate, 2,4'- and / or 4,4'-diphenylmethane diisocyanate (hereinafter abbreviated as MDI), 4,4'-diisocyanatobiphenyl, 3,3'-dimethyl-4,4'-diisocyanatobiphenyl, 3,3'-dimethyl-4,4'-diisocyanatodiphenylmethane, and 1,5-naphthylene diisocyanate. Among these, it is preferable to use MDI, which has excellent flexibility when made into a water-dispersible polyurethane.
[0049] Specific examples of the aliphatic diisocyanate having 2 or more and 18 or less carbon atoms include ethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, dodecamethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, lysine diisocyanate, 2,6-diisocyanatomethyl caproate, bis(2-isocyanatoethyl)carbonate, and 2-isocyanatoethyl-2,6-diisocyanatohexaate.
[0050] Specific examples of the alicyclic diisocyanate having 4 or more and 15 or less carbon atoms include isophorone diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, cyclohexylene diisocyanate, methylcyclohexylene diisocyanate, bis(2-isocyanatoethyl)-4-cyclohexylene-1,2-dicarboxylate, and 2,5- and / or 2,6-norbornane diisocyanate. Of these, it is preferable to use dicyclohexylmethane-4,4'-diisocyanate, which has excellent durability when made into a water-dispersible polyurethane.
[0051] Specific examples of the aromatic aliphatic diisocyanate having 8 to 15 carbon atoms include m- and / or p-xylylene diisocyanate, and α,α,α',α'-tetramethylxylylene diisocyanate.
[0052] (c) Compounds containing active hydrogen components having hydrophilic groups The active hydrogen component-containing compound having a hydrophilic group preferably used in the present embodiment includes a compound containing active hydrogen and one or more groups selected from the group consisting of nonionic groups, anionic groups, and cationic groups. These active hydrogen component-containing compounds can also be used in the state of a salt neutralized with a neutralizing agent. By using this active hydrogen component-containing compound having a hydrophilic group, the stability of the aqueous dispersion used in the manufacturing method of artificial leather can be improved.
[0053] Examples of compounds having a nonionic group and active hydrogen include compounds that contain two or more active hydrogen components or two or more isocyanate groups and have a polyoxyethylene glycol group or the like having a molecular weight of 250 or more and 9,000 or less on the side chain, and triols such as trimethylolpropane and trimethylolbutane.
[0054] Examples of compounds having an anionic group and active hydrogen include carboxyl group-containing compounds such as 2,2-dimethylolpropionic acid, 2,2-dimethylolbutanoic acid, and 2,2-dimethylolvaleric acid, and derivatives thereof; sulfonic acid group-containing compounds such as 1,3-phenylenediamine-4,6-disulfonic acid and 3-(2,3-dihydroxypropoxy)-1-propanesulfonic acid, and derivatives thereof; and salts of these compounds neutralized with a neutralizing agent.
[0055] Examples of compounds containing a cationic group and active hydrogen include tertiary amino group-containing compounds such as 3-dimethylaminopropanol, N-methyldiethanolamine, and N-propyldiethanolamine, and derivatives thereof.
[0056] (d) Chain extender Examples of chain extenders preferably used in this embodiment include water, low molecular weight diols such as "ethylene glycol, propylene glycol, 1,3-butylene glycol, 1,4-butanediol, 1,6-hexanediol, diethylene glycol, and neopentyl glycol," alicyclic diols such as "1,4-bis(hydroxymethyl)cyclohexane," aromatic diols such as "1,4-bis(hydroxyethyl)benzene," aliphatic diamines such as "ethylenediamine," alicyclic diamines such as "isophoronediamine," aromatic diamines such as "4,4'-diaminodiphenylmethane," aromatic aliphatic diamines such as "xylylenediamine," alkanolamines such as "ethanolamine," hydrazine, dihydrazides such as "adipic acid dihydrazide," and mixtures of two or more of these.
[0057] Of these, preferred chain extenders are water, low molecular weight diols and aromatic diamines, and more preferred are water, ethylene glycol, 1,4-butanediol, 4,4'-diaminodiphenylmethane and mixtures of two or more of these.
[0058] (e) Structure of polyurethane precursor As described above, the polyurethane precursor preferably used in the present embodiment is prepared by reacting the above-mentioned polymer polyol, an organic diisocyanate, and an active hydrogen component-containing compound having a hydrophilic group to form a hydrophilic prepolymer, and then adding and reacting a chain extender.
[0059] (f) Crosslinking agent The crosslinking agent used in this embodiment may have two or more reactive groups in the molecule that can react with the reactive group introduced into the polyurethane precursor, and specific examples include polyisocyanate crosslinking agents such as water-soluble isocyanate compounds and blocked isocyanate compounds, melamine crosslinking agents, oxazoline crosslinking agents, carbodiimide crosslinking agents, etc. The crosslinking agents may be used alone or in combination of two or more.
[0060] The water-soluble isocyanate compound has two or more isocyanate groups in the molecule, and examples of the water-soluble isocyanate compound include the above-mentioned organic polyisocyanate-containing compounds.
[0061] A blocked isocyanate compound has two or more blocked isocyanate groups in the molecule. The blocked isocyanate group refers to the organic polyisocyanate compound blocked with a blocking agent such as amines, phenols, imines, mercaptans, pyrazoles, oximes, active methylenes, etc.
[0062] The oxazoline-based crosslinking agent may be a compound having two or more oxazoline groups (oxazoline skeletons) in the molecule.
[0063] The carbodiimide crosslinking agent may be a compound having two or more carbodiimide groups in the molecule.
[0064] Among these, it is preferable to use a carbodiimide compound, which gives a water-dispersible polyurethane that is particularly excellent in durability and flexibility after the reaction.
[0065] (g) Structure of water-dispersible polyurethane The water-dispersed polyurethane preferably used in this embodiment preferably contains a component derived from polyether polyol and / or polycarbonate polyol from the viewpoint of flexibility and durability. The water-dispersed polyurethane contains a component derived from polyether polyol, and the degree of freedom of the ether bond is high, so that the glass transition temperature is low and the cohesive force is weak, so that the water-dispersed polyurethane has excellent flexibility. In addition, the water-dispersed polyurethane contains a component derived from polycarbonate polyol, and the high cohesive force of the carbonate group allows the water-dispersed polyurethane to have excellent water resistance, heat resistance, weather resistance, and mechanical properties.
[0066] As a method for confirming the constituents of the water-dispersible polyurethane (confirming that the water-dispersible polyurethane contains a constituent component derived from a polyester polyol and / or that the water-dispersible polyurethane contains a constituent component derived from a polycarbonate polyol), the polyester constituting the artificial leather can be dissolved, and the insoluble matter (water-dispersible polyurethane) can be analyzed by infrared spectroscopy (analytical equipment such as the "FT / IR 4000 series" manufactured by JASCO Corporation) or pyrolysis GC / MS analysis (analytical equipment such as the "GCMS-QP5050A" manufactured by Shimadzu Corporation). As a solvent capable of dissolving the polyester constituting the artificial leather, m-cresol or hexafluoroisopropanol can be used, but it is preferable to use hexafluoroisopropanol, which can be handled at room temperature.
[0067] The water-dispersible polyurethane used in the present embodiment preferably has an N-acylurea bond and / or an isourea bond. The N-acylurea bond and / or the isourea bond is formed by the reaction of the hydrophilic group with a crosslinking agent having a carbodiimide group, and by forming a crosslinked structure in the water-dispersible polyurethane, the durability of the water-dispersible polyurethane can be improved.
[0068] The presence of the above-mentioned N-acylurea group or isourea group in the water-dispersible polyurethane can be analyzed by performing, for example, a mapping process such as time-of-flight secondary ion mass spectrometry (TOF-SIMS analysis) (an analytical instrument such as the "TOF.SIMS 5" manufactured by ION-TOF) or infrared spectroscopy (an analytical instrument such as the "FT / IR 4000 series" manufactured by JASCO Corporation) on a cross section of the artificial leather.
[0069] In general, the content of the polymer elastomer in the artificial leather can be appropriately adjusted in consideration of the type of polymer elastomer used, the manufacturing method of the polymer elastomer, and the texture and physical properties, but in this embodiment, the content of the polymer elastomer is preferably 10% by mass or more and 50% by mass or less based on the mass of the artificial leather. By making the content of the polymer elastomer preferably 10% by mass or more, more preferably 15% by mass or more, the artificial leather can have excellent abrasion resistance. On the other hand, by making the content of the polymer elastomer preferably 50% by mass or less, more preferably 35% by mass or less, the artificial leather can have a soft texture.
[0070] In addition, the polymer elastomer may contain various additives depending on the purpose, for example, "inorganic and oxide-based" pigments, "phosphorus-, halogen-, and inorganic" flame retardants, "phenol-, sulfur-, and phosphorus-based" antioxidants, "benzotriazole-, benzophenone-, salicylate-, cyanoacrylate-, and oxalic acid anilide-based" ultraviolet absorbers, "hindered amine- and benzoate-based" light stabilizers, hydrolysis-resistant stabilizers such as polycarbodiimide, plasticizers, antistatic agents, surfactants, coagulation adjusters, and dyes.
[0071] [Artificial leather] The artificial leather of this embodiment includes the above-mentioned fiber entanglement body and polymer elastomer as components. In the artificial leather of this embodiment, it is preferable that at least one surface thereof has nap. Depending on the desired purpose, only one surface of the artificial leather may have nap, and it is also acceptable that both surfaces have nap. In the case where the surface has nap, the nap form preferably has a nap length and directional flexibility to the extent that a mark is left when the surface is traced with a finger, that is, the nap direction changes when the surface is traced with a finger, and the so-called finger mark is generated when the surface is traced with a finger, and the nap direction changes when the surface is traced with a finger, and the so-called finger mark is generated when the surface is traced with a finger.
[0072] More specifically, the length of the nap on the surface, i.e., the nap length, is preferably 200 μm or more and 500 μm or less. By making the nap length 200 μm or more, more preferably 220 μm or more, it is possible to obtain an artificial leather having an elegant suede-like surface quality and excellent touch feeling. On the other hand, by making the nap length 500 μm or less, more preferably 450 μm or less, it is possible to obtain an artificial leather having excellent abrasion resistance and also to suppress the deterioration of surface quality caused by entanglement of ultrafine fibers.
[0073] When at least one surface of the artificial leather has the above-mentioned napped surface, the nap length of the surface is a value measured and calculated by the following method.
[0074] (1) Use a lint brush or the like to raise the nap of the artificial leather, and then photograph a cross section perpendicular to the longitudinal direction of the artificial leather with a scanning electron microscope (SEM, for example, Keyence Corporation's "VHX-D500 / D510" model) at a magnification of 50 to 120 times. (2) In the SEM image, the bottom surface of the artificial leather (L in Fig. 1) is B ) parallel to the line (L in Fig. 1) A ) at 200 μm intervals on the bottom surface (L B ) 10 perpendicular lines (A1~A 10 )Pull. (3) Perpendicular line A1~A 10and a boundary line (L0) between the raised portion (1 in FIG. 1) and the base portion (2 in FIG. 1) other than the raised portion 1. 10 Mark the (4) Perpendicular line A1~A 10 and the tip of the hair standing portion 1 intersect at points Q1 to Q 10 Mark the (5) Let R1 be the distance between points P1 and Q1, and let P n and point Q n The distance between n Similarly, R 10 Then calculate the average (arithmetic mean).
[0075] The artificial leather of this embodiment has an apparent density of 0.30 g / cm 3 More than 0.50g / cm 3 The apparent density of the artificial leather is preferably 0.30 g / cm or less. 3 More preferably, 0.32 g / cm 3 By setting the apparent density to 0.50 g / cm or more, the artificial leather has excellent abrasion resistance. 3 Less than or equal to 0.45 g / cm 3 By satisfying the following conditions, the artificial leather will have a soft texture.
[0076] The artificial leather of this embodiment preferably has a thickness of 0.2 mm or more and 1.5 mm or less, as measured by "6.1.1 A method" of "6.1 Thickness (ISO method)" of JIS L1913:2010 "General nonwoven fabric test methods". When the thickness of the artificial leather is preferably 0.2 mm or more, more preferably 0.3 mm or more, the artificial leather not only has excellent processability during production, but also has a rich feel and excellent texture. On the other hand, when the thickness of the artificial leather is preferably 1.5 mm or less, more preferably 1.2 mm or less, the artificial leather has excellent moldability and flexibility.
[0077] In addition, in the abrasion resistance test of the artificial leather of this embodiment, measured by "8.19.5 E method (Martindale method)" of "8.19 Abrasion resistance and friction discoloration" of JIS L1096:2010 "Testing methods for woven and knitted fabrics", the abrasion loss of the artificial leather after abrasion 50,000 times at a pressing load of 12.0 kPa is preferably 30 mg or less, more preferably 27 mg or less, and even more preferably 25 mg or less. By having the abrasion loss of the artificial leather be 30 mg or less, contamination due to fluff shedding during actual use and deterioration of the appearance of the artificial leather are suppressed.
[0078] [Manufacturing method of artificial leather] The method for producing the artificial leather of the present embodiment includes a step of drawing an ultrafine fiber-developing fiber formed of an easily soluble polymer, which is a copolymer polyester copolymerized with a polyalkylene glycol having a number average molecular weight of 500 to 3500, and a poorly soluble polymer, to obtain a drawn composite fiber; a step of heating the drawn conjugated fiber under conditions such that the surface temperature of the drawn conjugated fiber is 40° C. or more and 80° C. or less, and then crimping the drawn conjugated fiber to obtain a crimped conjugated fiber; forming a fiber web from the crimped conjugated fibers and entangling the fiber web to form an entangled conjugated fiber body; forming a fiber-entangled body by generating ultrafine fibers having an average single fiber diameter of 0.1 μm or more and 10.0 μm or less from the composite fiber-entangled body; A step of providing a polymeric elastomer to the composite fiber entanglement or the fiber entanglement; The details of this preferred embodiment will be described below, but the scope of the following description is not intended to be limiting, and various modifications are possible within the scope of the present invention.
[0079] <Step of obtaining drawn composite fiber> In this process, first, an ultrafine fiber-developing fiber formed of a soluble polymer, which is a copolymer polyester copolymerized with a polyalkylene glycol having a number average molecular weight of 500 to 3500, and a poorly soluble polymer is drawn to obtain a drawn composite fiber. Here, in this embodiment, the ultrafine fiber-developing fiber refers to a fiber in which the soluble polymer is removed and the remaining poorly soluble polymer becomes an ultrafine fiber, such as an island-in-sea composite fiber or a core-sheath composite fiber. The soluble polymer is a resin described below that dissolves within 5 minutes when immersed in a solution such as an alkaline aqueous solution used to remove the soluble polymer from the ultrafine fiber-developing fiber. On the other hand, the poorly soluble polymer is a resin described below that does not dissolve in the above solution for 10 minutes or more.
[0080] (1) Easily soluble polymer Examples of readily soluble polymers for ultrafine fiber development include polylactic acid and copolymer polyesters. From the viewpoints of spinnability and ease of dissolution by alkali treatment, copolymer polyesters are preferably used.
[0081] When a copolymerized polyester is used, it is preferable that the copolymerized polyester is obtained by copolymerizing 3 mol % or more and 15 mol % or less of sodium 5-sulfoisophthalate as a copolymerization component. By setting the copolymerization amount of the sodium 5-sulfoisophthalate component to preferably 3 mol % or more, more preferably 5 mol % or more, sufficient alkali elution properties can be obtained. On the other hand, by setting the copolymerization amount of the sodium 5-sulfoisophthalate component to preferably 15 mol % or less, more preferably 13 mol % or less, thickening of the polyester is suppressed, and the effect of preventing thread breakage during spinning of ultrafine fiber development type fibers is achieved.
[0082] The copolymer polyester is preferably copolymerized with a polyalkylene glycol having a number average molecular weight of 500 or more and 3500 or less, more preferably in the range of 700 or more and 3000 or less. By setting the number average molecular weight of the polyalkylene glycol within the above range, the dispersibility of the polyalkylene glycol in the easily soluble polymer is improved, and excellent effects are achieved in terms of the spinnability and alkali elution property of the ultrafine fiber-developing fiber, and a uniform and sufficient sea-removal effect can be obtained during alkali treatment.
[0083] The copolymerization amount of polyalkylene glycol in the easily soluble polymer is preferably 0.1% by mass or more and 15% by mass or less. By making the copolymerization amount of polyalkylene glycol preferably 0.1% by mass or more, more preferably 1.5% by mass or more, the alkali elution property becomes good. On the other hand, by making the copolymerization amount of polyalkylene glycol preferably 15% by mass or less, more preferably 12% by mass or less, the effect of preventing thread breakage during spinning of ultrafine fiber development type fibers is achieved.
[0084] Examples of polyalkylene glycols include polyethylene glycol, polypropylene glycol, and polybutylene glycol, with polyethylene glycol being preferred because of its ease of use and ease of reduction in weight in an alkaline aqueous solution.
[0085] The easily soluble polymer constituting the ultrafine fiber development type fiber preferably contains a polyethylene terephthalate polyester having ethylene terephthalate units as a main repeating unit as one component, or may be a polyester in which a part of the terephthalic acid component is replaced with another bifunctional carboxylic acid component, or similarly, a polyester in which a part of the ethylene glycol component is replaced with another polyol component.
[0086] As the difunctional carboxylic acid other than terephthalic acid used in the present embodiment, for example, aromatic, aliphatic, and alicyclic difunctional carboxylic acids such as isophthalic acid, naphthalene dicarboxylic acid, diphenyl dicarboxylic acid, adipic acid, sebacic acid, and 1,4-cyclohexane dicarboxylic acid are preferably used. In addition, as the polyol compound other than ethylene glycol, for example, aliphatic, alicyclic, and aromatic polyol compounds such as tetramethylene glycol, hexamethylene glycol, cyclohexane-1,4-dimethanol, neopentyl glycol, bisphenol A, and bisphenol S are preferably used.
[0087] Furthermore, the easily soluble polymer constituting the ultrafine fiber-developing fiber and the poorly soluble polymer described below can contain inorganic particles such as titanium oxide particles, lubricants, pigments, heat stabilizers, ultraviolet absorbers, conductive agents, heat storage agents, antibacterial agents, and the like according to various purposes, within the scope of not impeding the object of the present invention.
[0088] (2) Poorly soluble polymer The hardly soluble polymer of the ultrafine fiber development type fiber may include polyester resin, polyamide resin, polyolefin resin, acrylic resin, polyphenylene sulfide resin, etc., which are listed as the thermoplastic resin constituting the ultrafine fiber. The polyester resin may include polyethylene terephthalate, polybutylene terephthalate, polytrimethylene terephthalate, polylactic acid, and mixtures and copolymers of these polyester resins. The polyamide resin may include polyamide 6, polyamide 66, polyamide 610, polyamide 12, and mixtures and copolymers of these polyamide resins. The polyolefin resin may include polyethylene, polypropylene, and mixtures and copolymers of these polyolefin resins. Among them, polyester resin is preferably used from the viewpoint of strength, dimensional stability, and heat resistance. The hardly soluble polymer may contain inorganic particles such as titanium oxide particles, lubricants, pigments, heat stabilizers, ultraviolet absorbers, conductive agents, heat storage agents, antibacterial agents, etc. according to various purposes.
[0089] (3) Ultrafine fiber Ultrafine fiber-producing fibers can be produced by a method using an islands-in-sea type composite spinneret or a sheath-core type composite spinneret, in which two components, a soluble polymer and a sparingly soluble polymer, are mutually arranged and spun, or a mixed spinning method in which two components, a soluble polymer and a sparingly soluble polymer, are mixed and spun, and from the viewpoint of obtaining ultrafine fibers with uniform single fiber fineness, islands-in-sea type composite fibers or sheath-core type composite fibers produced by a method using a polymer mutual arrangement are preferred.
[0090] The ultrafine fiber-developing fibers used in the artificial leather of this embodiment can be obtained by using a general composite spinneret in which a group of pipes is arranged, or a composite spinneret capable of forming various cross-sectional shapes by combining a metering plate having multiple metering holes for metering the polymer streams of each component and a confluence groove that joins the polymer streams discharged from the multiple metering holes with a distribution plate having multiple distribution holes, as described in JP 2011-174215 A.
[0091] The ratio of the soluble polymer to the sparingly soluble polymer in the ultrafine fiber is preferably 20% or more and 95% or less in terms of the mass ratio of the sparingly soluble polymer to the ultrafine fiber. By setting the mass ratio of the sparingly soluble polymer to be preferably 20% or more, more preferably 30% or more, the removal rate of the soluble polymer can be reduced, and productivity can be further improved. On the other hand, by setting the mass ratio of the sparingly soluble polymer to be preferably 95% or less, more preferably 90% or less, the joining of the sparingly soluble polymers can be prevented, and a decrease in surface quality can be suppressed.
[0092] The spinning speed for obtaining ultrafine fiber-developing fibers is preferably 500 m / min or more and 3000 m / min or less. By setting the spinning speed to preferably 500 m / min or more, more preferably 800 m / min or more, the average single fiber diameter of the ultrafine fibers can be easily set to 10.0 μm or less, and an artificial leather with a dense surface quality and excellent touch can be obtained. On the other hand, by setting the spinning speed to preferably 3000 m / min or less, more preferably 2000 m / min or less, the frequency of yarn breakage is reduced and productivity is further improved.
[0093] (4) Drawing of ultrafine fiber In this step, the ultrafine fiber-developing fiber is finally drawn to obtain a drawn composite fiber. At this time, the draw ratio is preferably 2.0 times or more and 4.5 times or less. By setting the draw ratio to preferably 2.0 times or more, more preferably 2.3 times or more, it is possible to obtain an ultrafine fiber-developing fiber having sufficient strength. On the other hand, by setting the draw ratio to preferably 4.5 times or less, more preferably 4.2 times or less, it is possible to achieve excellent stability during drawing processing.
[0094] The stretching temperature during the above stretching is preferably 50°C or higher and 80°C or lower. Here, the stretching temperature refers to the temperature of the heat source with which the ultrafine fiber development type fiber comes into contact during stretching, and specifically refers to the surface temperature of the roller in the case of roller stretching, the liquid temperature of the liquid bath in the case of liquid bath stretching, and the atmospheric temperature inside the steam box in the case of steam stretching. By setting the stretching temperature at preferably 50°C or higher, ultrafine fiber development type fiber with little orientation unevenness can be obtained. On the other hand, by setting the stretching temperature at preferably 80°C or lower, elution of the easily soluble polymer during stretching can be suppressed.
[0095] <Step for obtaining crimped composite fiber> In this step, the stretched conjugate fiber is heated under conditions such that the surface temperature of the stretched conjugate fiber is 40° C. or more and 80° C. or less, and then crimped to obtain a crimped conjugate fiber. In addition to adjusting the conditions such as the stretch ratio and stretching temperature, the heat treatment can control the degree of molecular orientation in the ultrafine fibers that constitute the artificial leather, and it is possible to obtain the artificial leather that has a dense and elegant surface quality and combines a good touch and abrasion resistance, which is the object of the present invention.
[0096] In this embodiment, the surface temperature of the drawn composite fiber during heating is preferably from 40° C. to 80° C., and more preferably from 45° C. to 70° C. By setting the heating temperature within the above range, it is possible to suppress the elution of the easily soluble polymer, and also to provide an ultrafine fiber-developing fiber with appropriate strength and elongation and shrinkage, which has the effect of excellent processability in the subsequent steps, and it is also possible to set the degree of molecular orientation in the ultrafine fibers, which is a feature of this embodiment, within a specific range.
[0097] In the method for producing an artificial leather according to the present embodiment, the tensile strength of the poorly soluble polymer portion of the stretched conjugate fiber or crimped conjugate fiber is preferably 3.0 cN / dtex or more. By making the tensile strength of the poorly soluble polymer portion preferably 3.0 cN / dtex or more, more preferably 3.2 cN / dtex or more, the abrasion resistance of the artificial leather can be improved and a decrease in friction fastness due to fiber shedding can be suppressed.
[0098] In this embodiment, the tensile strength of the sparingly soluble polymer portion of the drawn conjugate fiber or crimped conjugate fiber is calculated by the following method. (1) Ten pieces of 20 cm long stretched or crimped composite fiber are bundled together. (2) After dissolving and removing the easily soluble polymer from the sample (1), air dry it. (3) Conduct the test 10 times under the conditions of "8.5.1 Standard time test" in "8.5 Tensile strength and elongation" of JIS L1013:2010 "Test methods for chemical fiber filament yarn" with a grip length of 5 cm, a pulling speed of 5 cm / min, and a load of 2 N. (4) The arithmetic mean value (cN / dtex) of the test results obtained in (3) above shall be rounded off to one decimal place to determine the tensile strength of the sparingly soluble polymer portion constituting the drawn or crimped composite fiber.
[0099] <Step of forming a composite fiber entanglement> In this step, a fiber web is formed from the crimped conjugated fibers, and the fiber web is entangled to form an entangled conjugated fiber body. More specifically, the crimped conjugated fibers are opened, and then formed into a fiber web by a cross wrapper or the like, and the fiber web is entangled to form an entangled conjugated fiber body.
[0100] As a method for forming a fiber web and entangling the fiber web to obtain a composite fiber-entangled body, a needle punching process, a water jet punching process, etc. can be used. Among them, the needle punching process, which has a high entanglement efficiency, is preferable.
[0101] As for the form of the entangled composite fiber, either a short fiber entangled body or a long fiber entangled body can be used as described above. In the case of a short fiber entangled body, the number of fibers oriented in the thickness direction of the artificial leather is greater than in the case of a long fiber entangled body, and a highly dense feel can be obtained on the surface of the artificial leather when it is raised.
[0102] When the short fiber entangled body is produced, the obtained crimped composite fiber is cut to a predetermined length, and then opened, laminated, and entangled to obtain a short fiber entangled body. The crimping and cutting processes can be carried out by known methods.
[0103] The number of needle barbs (notches) in the needle used in the needle punching process is preferably 1 to 9. By preferably having 1 or more needle barbs, efficient fiber entanglement is possible. On the other hand, by preferably having 9 or less needle barbs, fiber damage can be suppressed.
[0104] The number of ultrafine fiber-producing fibers caught by the barb is determined by the shape of the barb and the diameter of the ultrafine fiber-producing fibers. Therefore, the barb shape of the needle used in the needle punching process is preferably one having a kick-up of 0 μm to 50 μm, an undercut angle of 0° to 40°, a throat depth of 40 μm to 80 μm, and a throat length of 0.5 mm to 1.0 mm.
[0105] The number of needle punches is 1000 / cm 2 More than 8000 pieces / cm 2 The number of punches is preferably 1000 / cm or less. 2 By setting the number of punches at 8000 / cm or more, a dense fiber entanglement can be obtained. 2 By setting the content to the range below, it is possible to prevent deterioration of processability, fiber damage, and reduction in strength.
[0106] In addition, when performing water jet punching, it is preferable to perform the treatment with water in the form of a columnar flow. Specifically, it is preferable to eject water from a nozzle having a diameter of 0.05 mm to 1.0 mm at a pressure of 2 MPa to 60 MPa.
[0107] The apparent density of the composite fiber entanglement consisting of ultrafine fiber expression type fibers after needle punching or water jet punching is 0.15 g / cm 3 More than 0.40g / cm 3 The apparent density of the composite fiber entanglement is preferably 0.15 g / cm or less. 3 More preferably, 0.20 g / cm 3 By setting the apparent density of the composite fiber entanglement body at 0.40 g / cm or more, an artificial leather having excellent durability and abrasion resistance can be obtained. 3 Less than or equal to 0.35 g / cm 3 By setting the above, it is possible to maintain space for applying the polymeric elastomer, so that the polymeric elastomer is applied uniformly, and an artificial leather with excellent resilience can be obtained.
[0108] The weight of the composite fiber entanglement is 200 g / m 2 More than 900g / m 2 The weight of the composite fiber entanglement is preferably 200 g / m or less. 2 More preferably, 250 g / m 2 By setting the weight per unit area of the composite fiber entanglement body at 900 g / m or more, an artificial leather having excellent abrasion resistance can be obtained. 2 Less than 800g / m 2 By satisfying the following conditions, a flexible artificial leather having excellent moldability can be obtained.
[0109] It is also a preferred embodiment that the composite fiber entanglement is subjected to a heat shrinkage treatment with hot water or steam in order to improve the denseness of the fibers.
[0110] Next, the composite fiber entanglement body can be impregnated with an aqueous solution of the water-soluble resin and dried to impart the water-soluble resin to the composite fiber entanglement body. By imparting the water-soluble resin to the composite fiber entanglement body, the fibers are fixed and the dimensional stability is improved.
[0111] <Step of forming ultrafine fibers and entangled fiber body> In this step, ultrafine fibers having an average single fiber diameter of 0.1 μm or more and 10.0 μm or less are produced from the entangled composite fibers to form a entangled fiber body.
[0112] The ultrafine fiber development treatment used in this embodiment does not require the use of an organic solvent. More specifically, if the easily soluble polymer is polylactic acid or a copolymer polyester, the treatment can be carried out by immersing a composite fiber entanglement body made of ultrafine fiber development type fibers in an alkaline aqueous solution to dissolve and remove the easily soluble polymer of the ultrafine fiber development type fibers. As the alkaline aqueous solution, a sodium hydroxide aqueous solution is preferably used because it makes it easier to treat salts generated by neutralization when treating waste liquid.
[0113] <Step of providing polymeric elastomer> Furthermore, in this step, a polymeric elastomer is applied to the composite fiber entanglement or the fiber entanglement. Specifically, a step of impregnating a solution of a polymeric elastomer and solidifying it to apply the polymeric elastomer is more preferable.
[0114] Methods for fixing the polymer elastomer to the entangled composite fiber body or the entangled fiber body include a wet coagulation method in which the entangled fiber body is impregnated with a solution of the polymer elastomer and then immersed in a coagulation bath to fix it, and a dry coagulation method in which the entangled fiber body is dried to fix it. These methods can be appropriately selected depending on the type of polymer elastomer to be applied.
[0115] As a solvent used when providing polyurethane as a polymeric elastomer, N,N'-dimethylformamide, dimethylsulfoxide, etc., or a water-dispersed polyurethane liquid in which polyurethane is dispersed in water as an emulsion, etc. are preferably used. Among them, from the viewpoint of environmental consideration, a water-dispersed polyurethane liquid is preferably used.
[0116] Here, the case has been described in which the step of imparting a polymer elastomer to the entangled fiber body is carried out after the step of expressing the ultrafine fibers to form the entangled fiber body. However, the polymer elastomer may be imparted to the entangled composite fiber body after the step of forming the entangled composite fiber body and before expressing the ultrafine fibers.
[0117] <Other finishing processes> In the method for producing the artificial leather of this embodiment, it is preferable to carry out various finishing steps, as in the case of general artificial leathers.
[0118] First, the method for producing an artificial leather according to the present embodiment preferably includes a dyeing step for dyeing the artificial leather. As the dyeing process, various methods commonly used in the art can be adopted, such as a flow dyeing process using a jigger dyeing machine or a flow dyeing machine, a dip dyeing process such as a thermosol dyeing process using a continuous dyeing machine, or a printing process on a napped surface using roller printing, screen printing, inkjet printing, sublimation printing, vacuum sublimation printing, etc. Among them, it is preferable to use a flow dyeing machine, since the unbrushed artificial leather or artificial leather can be softened by giving a kneading effect at the same time as the dyeing of the unbrushed artificial leather or artificial leather. In addition, various resin finishing processes can be applied after dyeing, if necessary.
[0119] In addition, finishing treatment may be carried out using, for example, a softener such as silicone, an antistatic agent, a water repellent, a flame retardant, a light fastener, an antibacterial agent, etc. in the same bath as dyeing or after dyeing.
[0120] In this embodiment, from the viewpoint of production efficiency, it is also preferable to cut the sheet in half in the thickness direction, regardless of whether it is before or after the dyeing step.
[0121] In the method for producing the artificial leather of the present embodiment, it is also preferable to include a nap raising step, regardless of whether it is before or after the dyeing step. The method for forming nap is not particularly limited, and various methods commonly used in this field, such as buffing with sandpaper, can be used. The nap raising treatment can be performed on only one surface of the artificial leather, or on both surfaces.
[0122] When the artificial leather is to be subjected to a nap raising treatment, a lubricant such as a silicone emulsion can be applied to the surface of the artificial leather before the nap raising treatment. Also, by applying an antistatic agent before the nap raising treatment, grinding powder generated from the artificial leather by grinding is less likely to accumulate on the sandpaper. In this way, the artificial leather is formed.
[0123] Furthermore, in the method for producing artificial leather of this embodiment, if necessary, the artificial leather can be subjected to post-processing such as hole-making such as perforation, embossing, laser processing, Pinsonic processing, and printing.
[0124] The artificial leather of the present embodiment obtained by the production method exemplified above has a dense and elegant surface quality and is excellent in moldability and abrasion resistance, and therefore can be used in a wide range of applications, such as automotive interior materials and furnishings, consumer electronics, clothing, and bags.
[0125] For example, automobile interior materials containing the artificial leather are preferable because they have a dense and elegant surface quality and can utilize the characteristics of excellent moldability and wear resistance. Such automobile interior materials are preferably used for automobile parts such as steering wheels, horn switches, shift knobs, dashboards, instrument panels, glove boxes, floor carpets, floor mats, ceiling linings, sun visors, and assist grips, and it is more preferable that at least a part of these automobile parts is the artificial leather. Note that the "automobile" in this embodiment is not limited to so-called general passenger cars, but also includes some industrial machines, construction machines, and agricultural machines that can carry humans or animals, such as excavators, crane trucks, tractors, and combines.
[0126] Clothing containing the artificial leather is also preferred because it has a dense and elegant surface quality and can take advantage of its excellent moldability and abrasion resistance. Examples of such clothing include tops such as T-shirts, polo shirts, dress shirts, blouses, cache-coeurs, cut-and-sewn tops, sweaters, vests, hoodies, sweatshirts, turtlenecks, cardigans, tank tops, and tube tops, outerwear such as coats, blazers, jackets, windbreakers, cloaks, capes, aprons, and mantles, trousers such as slacks, jeans, and shorts, skirts, dresses such as cocktail dresses, one-piece dresses, and gowns, ceremonial vestments, suits, uniforms, underwear, and even accessories such as hats, belts, scarves, and ties, as well as clothing materials and accessories such as buttons and pockets, and the linings of the above clothing items. EXAMPLES
[0127] Next, the artificial leather of the present invention will be described in more detail with reference to examples, but the present invention is not limited to these examples. [Measurement method] The evaluation methods and measurement conditions used in the examples are described below, except that, unless otherwise specified, the measurements of each physical property were performed according to the above-mentioned methods.
[0128] A. Average single fiber diameter of ultrafine fibers: In measuring the average single fiber diameter of ultrafine fibers, ultrafine fibers were observed using a digital microscope "VHX-D500 / D510" manufactured by Keyence Corporation, and the average single fiber diameter was calculated.
[0129] B. Molecular orientation in ultrafine fibers The degree of molecular orientation in the ultrafine fibers was measured under the following conditions using a laser Raman spectrometer "Ramanor T64000" manufactured by Jobin Yvon. Measurement mode: Raman microscopy Objective lens: x100 Beam diameter: 1μm Light source: Ar+ laser / 514.5nm Laser power: 50mW Diffraction grating: Spectrograph 1800gr / mm Slit: 100μm Detector: CCD (Jobin Yvon) 1024 x 256
[0130] C. Crystal orientation of ultrafine fibers: The degree of crystal orientation of the ultrafine fibers was measured under the following conditions using an X-ray generator "SmartLab" manufactured by Rigaku Corporation. X-ray generator: SmartLab (sealed tube type) X-ray source: CuKα (with Ni filter) Output: 40kV 50mA Detector: D / teX one-dimensional detector -Light receiving solar slit: 2.5° Scan method: β continuous scan Entrance slit: 0.5mmh x 0.55mmw Receiving slit: 5mm-5mm Measurement range (β): 90°~270° Measurement step(β): 0.5° Scan speed: 15° / min Diffraction peaks: (010) plane 2θ = approx. 17°, (100) plane 2θ = approx. 25°
[0131] D. Crystallite size of ultrafine fibers: The crystallite size of the ultrafine fibers was measured using an X-ray generator "SmartLab" manufactured by Rigaku Corporation under the following conditions. X-ray generator: SmartLab (sealed tube type) X-ray source: CuKα (with Ni filter) Output: 40kV 50mA Detector: D / teX one-dimensional detector -Light receiving solar slit: 2.5° Scan method: 2θ-θ continuous scan Entrance slit: 0.5mmh x 0.55mmw Receiving slit: 15mm-20mm Measurement range (2θ): 5°~60° Measurement step (2θ): 0.02° Scan speed: 1.5° / min ·Measurement direction: equator line
[0132] E. Abrasion loss of artificial leather (abrasion resistance): The Martindale abrasion tester used was the James H. Heal & Co. Model 406, and the standard abrasion cloth used was the same company's ABRASTIVE CLOTH SM25. The artificial leather was subjected to a load of 12.0 kPa and abrasion was performed 50,000 times. The weight loss due to abrasion was calculated using the following formula, using the mass of the artificial leather before and after abrasion. Abrasion loss (mg) = mass before abrasion (mg) - mass after abrasion (mg) The abrasion loss (mg) was rounded off to the first decimal place, and artificial leather with an abrasion loss of 30 mg or less was deemed to have passed the test.
[0133] F. Artificial leather feel: A total of 20 people, 10 healthy adult males and 10 healthy adult females, were used as evaluators to make the following tactile judgments, and the most common evaluation was determined as the touch of the artificial leather. In the case of a tie, the higher evaluation was determined as the touch of the artificial leather. In this embodiment, a good level was determined as "A or B." A: It feels very smooth to the touch. B: Smooth to the touch. C: Rough texture. D: Very rough to the touch.
[0134] G. Surface quality of artificial leather: A total of 20 healthy adult males and females, 10 each, were used as evaluators to visually judge the following evaluations, and the most common evaluation was determined as the surface quality of the artificial leather. In the case of a tie in the evaluations, the higher evaluation was determined as the surface quality of the artificial leather. In this embodiment, a good level was determined as "A or B." A: Dense and has very good surface quality B: Dense and good surface quality C: Poor surface quality with poor density D: The surface lacks density and is of very poor quality.
[0135] [Copolymer polyester] The copolymer polyesters used in the examples and comparative examples are as follows. Copolymer PET-A: A copolymer polyester copolymerized with 8 mol % of sodium 5-sulfoisophthalate and 9 mass % of polyethylene glycol having a number average molecular weight of 1,000. Copolymer PET-B: A copolymer polyester copolymerized with 8 mol % of sodium 5-sulfoisophthalate and 9 mass % of polyethylene glycol having a number average molecular weight of 3,000. Copolymer PET-C: A copolymer polyester copolymerized with 6 mol % of sodium 5-sulfoisophthalate and 9 mass % of polyethylene glycol with a number average molecular weight of 2000. Copolymer PET-D: Copolymer polyester copolymerized with 8 mol % of sodium 5-sulfoisophthalate (polyethylene glycol is not copolymerized). Copolymer PET-E: A copolymer polyester copolymerized with 8 mol % of sodium 5-sulfoisophthalate and 9 mass % of polyethylene glycol with a number average molecular weight of 10,000.
[0136] [Example 1] (Step of Obtaining Stretched Composite Fiber) Polyethylene terephthalate (abbreviated as "PET" in Tables 1 and 2) with an intrinsic viscosity of 0.73 was used as the poorly soluble polymer (island component), and copolymer polyester "copolymer PET-A" was used as the readily soluble polymer (sea component). Using an islands-in-sea composite spinneret with 16 islands / hole, melt spinning was performed under the following conditions: spinning temperature: 285°C, poorly soluble polymer / readily soluble polymer mass ratio: 80 / 20, output rate: 1.6 g / min / hole, spinning speed: 1100 m / min. The fiber was then stretched 3.8 times in an oil bath at 65°C to obtain a stretched composite fiber.
[0137] (Step for obtaining crimped composite fiber) The drawn conjugated fiber was heated under conditions such that the surface temperature of the drawn conjugated fiber was 45° C. Then, the drawn conjugated fiber after the heat treatment was subjected to a crimping process using a push-in type crimper to obtain a crimped conjugated fiber.
[0138] (Step of forming a composite fiber entanglement) The crimped composite fiber was cut to a length of 51 mm to obtain raw cotton of islands-in-the-sea type composite fiber (crimped composite fiber) with a single fiber fineness of 4.4 dtex. Next, the raw cotton was used to form a fiber web through carding and cross-wrapping processes, and the fiber web was then cut into a 3,500 fiber / cm 2 The number of punches is 650g / m2. 2 The thickness is 2.5 mm and the apparent density is 0.26 g / cm 3 Thus, a composite fiber entanglement was obtained. The composite fiber entanglement obtained as described above was immersed in hot water at 98° C. for 2 minutes for shrinkage treatment.
[0139] (Step of applying polymeric elastomer) An aqueous dispersion was prepared containing 11 parts by mass of a polyurethane precursor consisting of polytetramethylene glycol as a polymer polyol, MDI as an organic diisocyanate, 2,2-dimethylolpropionic acid as an active hydrogen component-containing compound having a hydrophilic group, and ethylene glycol as a chain extender, 1 part by mass of a carbodiimide-based crosslinking agent, 5 parts by mass of sodium sulfate, and 83 parts by mass of water. The aqueous dispersion was then impregnated into the above-mentioned shrunk-treated composite fiber entanglement, squeezed with a mangle, and dried with hot air at 120°C for 20 minutes to solidify the polyurethane precursor, thereby solidifying the polyurethane, and obtaining a sheet with polyurethane having a crosslinked structure consisting of N-acylurea bonds and / or isourea bonds.
[0140] (Step of forming ultrafine fibers to form a fiber entanglement) The polyurethane-coated sheet was immersed in a 5% aqueous sodium hydroxide solution and then heat-treated with steam at 95° C. for 10 minutes to alkaline-decompose the sea component of the islands-in-sea composite fiber. Next, the excess sodium hydroxide and sodium sulfate were washed off with water, and the sheet was dried in a dryer at 160° C. for 10 minutes to obtain a fiber-entangled body made of ultrafine fibers to which polyurethane was applied.
[0141] (Other finishing processes) The fiber entanglement composed of ultrafine fibers to which the polyurethane was applied was cut in half perpendicular to the thickness direction, and then the surface opposite to the surface formed by the cutting in half (non-cut surface) was ground with endless sandpaper having a grit size of 120 to perform a nap-raising treatment, thereby obtaining a napped sheet having a thickness of 0.70 mm.
[0142] The napped sheet obtained as described above was dyed at 120°C using a jet dyeing machine, and then dried in a dryer to obtain an artificial leather. The results are shown in Table 1. The artificial leather obtained had a dense and elegant surface quality, a good touch, and excellent abrasion resistance.
[0143] [Example 2] In the above (step of obtaining crimped conjugated fibers), the stretched conjugated fibers were heated under conditions that would result in a surface temperature of 70° C., instead of 45° C., in order to obtain artificial leather in the same manner as in Example 1. The results are shown in Table 1. The obtained artificial leather had a dense and elegant surface quality, a good touch, and excellent abrasion resistance.
[0144] [Example 3] An artificial leather was obtained in the same manner as in Example 1, except that in the above (step of obtaining drawn composite fiber), "copolymerized PET-A" was used as the sea component, but was changed to "copolymerized PET-B". The results are shown in Table 1. The obtained artificial leather had a dense and elegant surface quality, a good touch feeling, and excellent abrasion resistance.
[0145] [Example 4] An artificial leather was obtained in the same manner as in Example 3, except that in the above (step of obtaining crimped conjugated fibers), the heating conditions were changed from 45° C., under which the surface temperature of the drawn conjugated fibers was increased to 70° C. The results are shown in Table 1. The obtained artificial leather had a dense and elegant surface quality, a good touch, and excellent abrasion resistance.
[0146] [Example 5] An artificial leather was obtained in the same manner as in Example 1, except that in the above (step of obtaining drawn composite fiber), "copolymerized PET-A" was used as the sea component, but was changed to "copolymerized PET-C." The results are shown in Table 1. The obtained artificial leather had a dense and elegant surface quality, a good touch feeling, and excellent abrasion resistance.
[0147] [Example 6] An artificial leather was obtained in the same manner as in Example 5, except that in the above (step of obtaining drawn conjugate fiber), the drawing temperature was changed from 65° C. to 75° C., and in the above (step of obtaining crimped conjugate fiber), the heating conditions were changed from 45° C. to 70° C., resulting in a surface temperature of the drawn conjugate fiber. The results are shown in Table 1. The obtained artificial leather had a dense and elegant surface quality, a good touch, and excellent abrasion resistance.
[0148] [Example 7] An artificial leather was obtained in the same manner as in Example 1, except that in the above (step of obtaining drawn composite fiber), the draw ratio was changed from 3.8 times to 2.1 times. The results are shown in Table 1. The obtained artificial leather was slightly inferior in abrasion resistance to the artificial leather of Example 1, but had a dense and elegant surface quality and a good touch.
[0149] [Example 8] In the above (step of obtaining drawn conjugate fiber), spinning was performed under conditions of a spinning speed of 1100 m / min, but was changed to conditions of 3000 m / min, drawing temperature was performed under conditions of 65°C, but was changed to conditions of 80°C, and heating was performed under conditions of a surface temperature of the drawn conjugate fiber under conditions of 45°C, but was changed to conditions of 80°C in the above (step of obtaining crimped conjugate fiber). Except for these, an artificial leather was obtained in the same manner as in Example 1. The results are shown in Table 1. The obtained artificial leather had excellent abrasion resistance, although it was slightly inferior to the artificial leather of Example 1 in surface quality and touch.
[0150] [Example 9] An artificial leather was obtained in the same manner as in Example 1, except that in the above (other finishing steps), the sandpaper grit was changed from 120 to 180. The results are shown in Table 1. Although the obtained artificial leather was slightly inferior in touch to the artificial leather of Example 1, it had a dense and elegant surface quality and excellent abrasion resistance.
[0151] [Table 1]
[0152] [Comparative Example 1] An artificial leather was obtained in the same manner as in Example 1, except that in the above (step of obtaining drawn composite fiber), "copolymerized PET-A" was used as the sea component, but "copolymerized PET-D" was used instead. The results are shown in Table 2. The artificial leather obtained had a dense and elegant surface quality and a good touch, but was inferior in abrasion resistance to the artificial leather of Example 1.
[0153] [Comparative Example 2] An artificial leather was obtained in the same manner as in Example 1, except that in the above (step of obtaining drawn composite fiber), "copolymerized PET-A" was used as the sea component, but was replaced with "copolymerized PET-E". The results are shown in Table 2. The artificial leather obtained had a dense and elegant surface quality and excellent abrasion resistance, but was inferior in touch compared to the artificial leather of Example 1.
[0154] [Comparative Example 3] In the above (step of obtaining drawn conjugate fiber), the drawing temperature was changed from 65°C to 90°C, and in the above (step of obtaining crimped conjugate fiber), the heating conditions were changed from 45°C to 90°C. An artificial leather was obtained in the same manner as in Example 1. However, when the drawn conjugate fiber that had been subjected to the (step of obtaining drawn conjugate fiber) was subjected to the (step of obtaining crimped conjugate fiber), the sea component dissolved out, and the crimping process could not be performed using a push-in crimper, and the subsequent steps could not be carried out. The results are shown in Table 2.
[0155] [Comparative Example 4] In the above (step of obtaining crimped conjugated fibers), the stretched conjugated fibers were heated under conditions that would bring the surface temperature to 45°C, but instead, heating was not performed, and the stretched conjugated fibers without being heated were directly subjected to a crimping process using a push-in type crimper. An attempt was made to obtain artificial leather in the same manner as in Example 1. However, no crimp was observed in the stretched conjugated fibers, and the raw cotton obtained by cutting wrapped around a roller in the carding process, so that it was not possible to continue with the steps subsequent to (the step of forming a conjugated fiber entanglement). The results are shown in Table 2.
[0156] [Table 2]
[0157] Although the present invention has been described in detail with reference to specific embodiments, it is apparent to those skilled in the art that various changes and modifications can be made without departing from the spirit and scope of the present invention. This application is based on a Japanese patent application (Patent Application No. 2023-016558) filed on February 7, 2023, and is incorporated by reference in its entirety. In addition, all references cited herein are incorporated in their entirety. [Explanation of symbols]
[0158] 1: Pierrection part 2: Base part L A :Bottom L B A line parallel to L B :Bottom L0: Boundary between the hair-standing part 1 and the base part 2 A n (n is an integer between 1 and 10): Bottom L B Perpendicular to P n (n is an integer between 1 and 10): Perpendicular A n and boundary line L0 intersect Q n (n is an integer between 1 and 10): Perpendicular A n and the tip of the hair-raising portion 1 intersect R n (n is an integer between 1 and 10): Point P n and point Q n Distance
Claims
1. An artificial leather comprising, as components, a fiber-entangled body made of ultrafine fibers containing a thermoplastic resin and having an average single fiber diameter of 0.1 μm or more and 10.0 μm or less, and a polymer elastomer, wherein the thermoplastic resin is polyethylene terephthalate, at least one surface of the artificial leather has nap, the nap length of the surface being 200 μm or more and 500 μm or less, and the degree of molecular orientation of the ultrafine fibers being 6.5 or more and 9.0 or less.
2. Artificial leather as described in claim 1, wherein the crystal orientation degree of the (010) plane and the crystal orientation degree of the (100) plane in the fiber structure are 0.80 or more and 0.95 or less.
3. An artificial leather as described in claim 1 or 2, wherein the crystallite size of the (010) plane in the fiber structure is 2.0 nm or more and 5.0 nm or less, and the crystallite size of the (100) plane is 1.0 nm or more and 4.0 nm or less.
4. A step of drawing an ultrafine fiber-producing fiber formed of an easily soluble polymer, which is a copolymer polyester copolymerized with a polyalkylene glycol having a number average molecular weight of 500 to 3,500, and a poorly soluble polymer, to obtain a drawn conjugated fiber; a step of heating the drawn conjugated fiber under conditions such that the surface temperature of the drawn conjugated fiber is 40° C. or more and 80° C. or less, and then crimping the drawn conjugated fiber to obtain a crimped conjugated fiber; forming a fiber web from the crimped conjugated fibers and entangling the fiber web to form an entangled conjugated fiber body; forming a fiber-entangled body by expressing ultrafine fibers having an average single fiber diameter of 0.1 μm or more and 10.0 μm or less from the composite fiber-entangled body; providing a polymeric elastomer to the composite fiber entanglement or the fiber entanglement; The raising process and The method for producing the artificial leather according to claim 1 or 2, comprising:
5. An automobile interior material comprising the artificial leather according to claim 1 or 2.
6. An automobile part comprising the artificial leather according to claim 1 or 2.
7. 3. Clothing comprising the artificial leather according to claim 1 or 2.
Citation Information
Patent Citations
Production of leather-like sheet
JP2001055670A
Leather-like sheet and clothes
JP2011140727A
Conjugated fiber and substrate for artificial leather using the same
JP2014047441A
Ultra-fine fiber, substrate for artificial leather and artificial leather
JP2014231650A
Artificial leather and method for producing the same
JP2021155885A